Pendampingan Pengelolaan Website Sekolah Berbasis Content Management System di SD Xaverius 9 Palembang - Ria Triayomi; Stefanus Setyo Wibagso; Sukarman Sukarman; Ignasius Putera Setiahati; Geovani Lili Sugiarti; Natalia Devita Ningrum; Emilia Esti Putri Utaminingrum (Universitas Majalengka, 2023)
Community service was carried out by a team of lecturers from PGSD Study Program and Information Systems Study Program with Partner Schools at Xaverius 9 Elementary School Palembang.